Air pollution dispersion inside a street canyon of Göttinger Strasse (Hannover, Germany): New results of the analysis of full scale data - Mazzeo, Nicolas Antonio (2010)
This study analyses the interactions between pollutant concentrations inside a street canyon, and wind and traffic dispersive air motions. Air pollutant concentrations, meteorological parameters and traffic flow continuously measured in Göttinger Strasse (Hannover, Germany) were used in calculations. Parameters included in the inverse proportionality between concentration and a dispersive velocity scale were evaluated using statistical methods, for windward and leeward conditions. For leeward conditions, a 'critical wind speed' is defined as the roof-level wind speed at which traffic and wind induced turbulences inside the street canyon are equal. It varies with traffic density between 2 m s-1 and 4.5 m s-1.